2018
DOI: 10.1021/acs.cgd.8b00856
|View full text |Cite
|
Sign up to set email alerts
|

Role of Additives during Deracemization Using Temperature Cycling

Abstract: Temperature cycling, alongside Viedma ripening, has been established as a reliable method for deracemizing racemic mixtures of chiral compounds that crystallize as a conglomerate. Here we report that the speed of temperature cycling can be increased by using chiral additives. We also demonstrate that the chirality of the additive determines the final enantiomeric state of the solid phase. Viedma ripening experiments using equivalent conditions, with and without chiral additives, are always found to be slower.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 24 publications
(34 reference statements)
0
33
0
Order By: Relevance
“…already showed that the presence of small, chiral impurities can steer the outcome of the deracemization and can speed up the process . As recently reported, a very small amount of chiral impurities can already be sufficient to halve the deracemization time …”
Section: Resultsmentioning
confidence: 82%
See 1 more Smart Citation
“…already showed that the presence of small, chiral impurities can steer the outcome of the deracemization and can speed up the process . As recently reported, a very small amount of chiral impurities can already be sufficient to halve the deracemization time …”
Section: Resultsmentioning
confidence: 82%
“…[30] As recently reported, a very small amount of chiral impurities can already be sufficient to halve the deracemization time. [31]…”
Section: Deracemization Using Viedmar Ipeningmentioning
confidence: 99%
“…For example, temperature-cycle-induced deracemization (TCID) is a process that converts a racemic mixture of the substrate to a nearly pure enantiomer in the solid phase without any external chiral source through temperature cycling. 1,[6][7][8][9][10][11] Scheme 1. Schematic representations of PC, TCID, and SOAT process.…”
Section: Introductionmentioning
confidence: 99%
“…Although TCID features simple steps in its realization, the key elements of the controlling mechanism of this relatively recent deracemization technique have not been completely established yet. Operating parameters such as the impact of solid mass involved in the thermal cycles, the amount of catalyst, the cooling rate, the suspension volume, the initial enantiomeric excess, the amplitude of the sweeps, the racemization rate, and the use of additives as growth inhibitors have been studied previously. Moreover, several computational studies have attributed the observed chiral enrichment to the crystallization step occurring during the cooling stage.…”
Section: Introductionmentioning
confidence: 99%